Phytoremediation of partially treated wastewater by chlorella vulgaris - Al-Mamun, Abdullah; Amid , Azura; Karim , Imtinan A.; Samiur Rashid, Md. Shah (2012)
Excessive pollutants (including nutrients) affect aquatic lives and environment in various ways. There are certain plants capable of removing pollutants from water. Phytoremediation is an alternate way to reduce nutrients from contaminated medium. Microalgae can be used for phytoremediation to reduce the nutrient content in the wastewater due to their (algae’s) ability to assimilate nutrients into the cells. In this study, microalgae (Chlorella vulgaris) was used to determine the removal efficiencies for pollutants, such as chemical oxygen demand (COD), total nitrogen (TN) and total phosphorus (TP). The Chlorella vulgaris was cultured in the shake flasks that contained wastewater in the presence of artificial light. It gave the maximum biomass algal production (200 mg/L) within five days, whereas the maximum removal percentage of TN and TP were within 83.1% and 91.2%, respectively. The optimum detention period for the maximum phytoremediation is found to varie within 10 and 14 days. Based on the laboratory scale study under controlled environment, it can be concluded that Chlorella vulgaris has the potential to reduce nutrient content of wastewater.